RETRACTED: Adherence to lifelines diet score and risk factors of metabolic syndrome among overweight and obese adults: A cross-sectional study - Akhavanfar, Roozbeh; Hojati, Ali; Kahrizi, Mohammad Saeed; Farhangi, Mahdieh Abbasalizad; Ardekani, Abnoos Mokhtari (Frontiers in Nutrition, 2022)
Background Metabolic syndrome (MetS) is one of the most significant public health issues worldwide, and diet quality is an important controllable environmental factor influencing the incidence of MetS. Numerous dietary scores have been established to assess compliance with dietary recommendations or eating patterns, many of which are not entirely food-based. Hence, Lifelines Diet Score (LLDS) was developed in response to the shortcomings of existing tools. This study aimed to assess any possible links between total food quality and cardiometabolic risk factors among overweight and obese adults. Methods This cross-sectional study included 338 overweight and obese individuals [body mass index (BMI) > 25 kg/m2] aged 20–50 years in Tabriz, Iran. To collect dietary data, we used a validated semi-quantitative Food Frequency Questionnaire (FFQ) for Iranian population. Enzymatic-colorimetric methods were used to assess serum glucose and lipids, and enzyme-linked immunosorbent assay (ELISA) kits were used to measure insulin levels. In addition, the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) and Quantitative Insulin Sensitivity Check Index (QUICKI) were calculated. Results BMI and hip circumference (HC) were significantly different (P < 0.05) amongst LLDS tertiles. Adherence to the highest tertile of LLDS was associated with lower SBP, and the subjects in higher LLDS tertiles significantly had lower systolic blood pressure (SBP) (P = 0.04). Triglyceride (TG) levels were also lower in the third tertile of LLDS with a near-significant P-value (P = 0.05). Conclusion According to our results, a higher diet quality score, determined by LLDS, can be associated with a lower risk of MetS. Further experimental and longitudinal studies are needed to better understand this relationship.